Case report: Restrictive cardiomyopathy presenting with complete thromboembolism occlusion of the terminal part of the abdominal aorta in a preadolescent Saudi girl - Al-Shammari, Ahmad A.; Muslim, Rawan Al; Almuslim, Jenan; Elashaal, Ehab; Lardhi, Haitham; AlQahtani, Saleh A.; AlBassam, Bassam N.; Lardhi, Amer (Frontiers in Pediatrics, 2022)
Restrictive cardiomyopathy (RCM) is a rare disease in children, accounting for less than 5% of all pediatric cardiomyopathies. It may be idiopathic or may be a secondary to a systemic disease. The disease is characterized by normal systolic function with impaired ventricular filling caused by stiff ventricular walls. Children with RCM often present with symptoms of exercise intolerance, shortness of breath, weakness, and chest discomfort. Thromboembolism events are an unusual presentation of RCM. We are reporting a preadolescent female from the eastern province of Saudi Arabia who presented with sudden right lower limb swelling, paresthesia, and pain caused by a complete occlusion of the terminal part of the abdominal aorta and both common iliac arteries. Echocardiography revealed dilated atria, normal ventricle dimensions and two floating thrombi in the left atrium. The patient was successfully managed with an anticoagulant, surgical thrombectomy and cardiac transplantation.